Without words to get in the way: Symbolic interaction in prison-based animal programs - Furst, Gennifer (Qualitative Sociology Review, 2007)
George H. Mead ([1934] 1967) contended a person’s sense of self develops from language-based interactions with other humans in society. According to contemporary sociologists, a person’s sense of self is also influenced by non-verbal interactions with human and non-human animals. The present research extends Sanders (1993) work that examined how dog owners relate to their pets and come to develop a unique social identity for them. Through interviews with participants in prison-based animal programs (PAPs), this research explores whether inmates engaged in a similar process of assigning the animals with which they work a human-like identity. The implications of the relationships that develop in terms of desistance, which Maruna (2001) argued requires a redefinition of a person’s self-identity, are discussed.